PENGARUH BUDAYA ORGANISASI DAN LEARNING ORGANIZATION TERHADAP KINERJA ORGANISASI PADA KANTOR PELAYANAN DAN PENGAWASAN BEA DAN CUKAI TIPE MADYA PABEAN BANDAR LAMPUNG - Ine Mariane; Muhammad Galih Permadi (e-JKPP, 2023)
The purpose of this study was to determine and analyse the effect of organisational culture and learning organisation on organisational performance at Bandar Lampung Customs and Excise. The sample used in this study was 51 respondents from a total population of 145 employees of Bandar Lampung Customs and Excise. The data collection method was obtained directly using a questionnaire to Bandar Lampung Customs and Excise employees. The data in this study were processed using multiple linear regression analysis using the help of the SPSS v 22 programme. The results of this study indicate that: there is a positive and significant effect of organisational culture on organisational performance, there is a positive and significant effect of learning organisation on organisational performance, organisational culture and learning organisation together have a positive and significant effect on organisational performance at Bandar Lampung Customs and Excise. This means that if organisational culture and learning organisation are jointly improved, organisational performance will also improve.